β-caryophyllene as an attractant for the cacao mirid bug, Helopeltis bakeri Poppius (Hemiptera: Miridae), and chemodiversity of its host plant volatiles - Tavera, Mary Angelique A.; Dela Cruz, Maria Criselda V.; Santos, Kris Lord T.; Amalin, Divina M.; Janairo, Jose Isagani B. (Frontiers in Agronomy, 2023)
The cacao mirid bug, Helopeltis bakeri, is a major insect pest of cacao in the Philippines. It feeds on pods causing puncture wounds that become necrotic lesions and may lead eventually to pod abortion. There is currently no semiochemical-based system developed for the monitoring and control of H. bakeri. Here, we report a kairomone identified from host plants of H. bakeri as a potential attractant. Volatile components were extracted using solid-phase microextraction (100-µm polydimethylsiloxane) and analyzed by gas chromatography - mass spectrometry. Chemodiversity analysis considering compound richness, evenness, and disparity showed similar phytochemical diversity among the six host plants, suggesting that chemodiversity is a factor in the host selection behavior of H. bakeri. Comparison of volatiles revealed that β-caryophyllene was present in all host plants. Using a wind tunnel, an impregnated lure containing 90 µg β-caryophyllene showed the highest attraction to adult H. bakeri. The results show the potential of β-caryophyllene as attractant that can be used in the development of kairomone-based trapping systems for H. bakeri as part of a holistic integrated pest management system for cacao.